Development of MEMS piezoelectronic energy harvesting device for wireless condition monitoring - Aliza 'Aini binti Md Ralib @ Md Raghib (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Microelectromechanical system (MEMS) vibration based energy harvesters have become significantly popular due to the growing demand of wireless sensor networks which need miniature, portable, long lasting and easily recharged sources of power. Usage of hazardous batteries is an unacceptable solution to power up the densely populated nodes due to their bulky sizes and high battery replacement cost. Piezoelectric devices are the perfect candidate for implementation in micro generators as they are easily fabricated, are silicon compatible and demonstrate high efficiencies for mechanical to electrical energy conversion. This work presents the design, simulation and fabrication of MEMS piezoelectric energy harvesters. The energy harvester was formed using Aluminium doped Zinc Oxide (AZO) cantilever beams with either Aluminium or Steel contacts. FEM simulation analysis was done to obtain the resonance frequency that provides maximum displacement of vibration and maximum output power. AZO/Steel and Al/AZO/Al/Si structures were successfully simulated, fabricated and experimentally measured. The fabricated AZO/Steel beam produced 4.2 Vs/m2 at the resonant frequency of 137.157 Hz. The Al/AZO/Al/Si beam operates at higher frequencies where it produced 3.2 V AC output voltages at resonance frequencies of 8.026 MHz. The proposed designs can be positioned on a gas turbine in power plant where at a critical vibration pattern it will generate power to activate a wireless sensor to caution for maintenance.